Analisis Stuktur dan Fungsi Mantra Singlar, Jampe, dan Ajian di Desa Cikedokan, Kecamatan Cikarang Barat, Kabupaten Karawang, dan Rekomendasinya Sebagai Materi Ajar Puisi Rakyat dI SMP Kelas VII - Audrey Tiara Rabhany; Imam Muhtarom; Daman Huri (Pusat Riset dan Inovasi Nasional, 2026)
This study examines the singlar, jampe, and ajian mantras as part of the oral literature that is still alive in the community of Cikedokan Village, West Cikarang District, Bekasi Regency. The study was conducted because the mantra tradition is a cultural heritage that is starting to be eroded by the development of the times so it needs to be recognized, analyzed, and utilized as a learning resource. The purpose of this study is to describe the physical structure and inner structure of mantras, identify the function of mantras in community life, and recommend the results of the study as teaching materials for folk poetry for seventh grade junior high school students. This study uses a qualitative approach with a descriptive analysis method. Data were obtained through interviews, recordings, and notes on mantra utterances. Data analysis was carried out through the stages of data reduction, classification, analysis, data presentation, and drawing conclusions. The results show that the singlar, jampe, and ajian mantras have a physical structure in the form of vocabulary, diction, denotation-connotation, figurative language, and imagery, as well as an inner structure that includes themes, feelings, tones, and messages. The functions of mantras include educational tools, entertainment, and strengthening social solidarity in the community. This study also found a combination of local Sundanese cultural elements with Islamic values ​​in the practice of mantras. Based on these results, the singlar, jampe, and ajian mantras are considered worthy of being recommended as folk poetry teaching materials because they contain cultural, linguistic, and character values ​​that are relevant to Indonesian language learning in junior high schools.